2011
DOI: 10.1002/jmri.22532
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular outflow tract obstruction as a confounding factor in the assessment of the impact of pulmonary regurgitation on the right ventricular size and function in patients after repair of tetralogy of fallot

Abstract: Purpose: To compare right ventricular (RV) size and function between patients with combined pulmonary regurgitation (PR) plus RV outflow tract (RVOT) obstruction (RVOTO) and patients with isolated PR. Materials and Methods:Consecutive individuals with significant PR (PR fraction !20%) after tetralogy of Fallot (TOF) repair who underwent cardiovascular magnetic resonance (CMR) were included. Patients with additional hemodynamic abnormalities (residual ventricular septal defect, extracardiac shunt, and/or more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
5
14
1
Order By: Relevance
“…Similarly to our findings, a previous study in patients with repaired TOF found no differences in regurgitant fraction between those with and without RVOT obstruction. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly to our findings, a previous study in patients with repaired TOF found no differences in regurgitant fraction between those with and without RVOT obstruction. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Selected data on patients with repaired TOF undergoing CMR imaging study in our center were published previously. [9][10][11][12] In particular, we previously analyzed factors associated with biventricular dysfunction in the same study population (31 patients with biventricular dysfunction and 65 patients with normal biventricular systolic functions were selected out of a group of 146 patient; unpublished data).…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
“…Nevertheless, we and other investigators have previously demonstrated that patients after TOF repair with coexisting RVOT obstruction (including branch pulmonary stenosis) had lower RVEDV compared with patients without obstruction. 11,33 Moreover, those with significant PR and concomitant RVOT obstruction (including but not limited to branch pulmonary stenosis) had higher RVEF in comparison with patients with isolated PR. 11 The relationship between various types and severity degrees of RVOT obstruction and ventricular function should be adequately addressed in further studies.…”
Section: Determinants Of Lvef and Rvef: Multivariate Analysismentioning
confidence: 99%
See 2 more Smart Citations